PhD and DBA: are they different? / Kuldip Singh - Singh, Kuldip (Universiti Teknologi MARA, Sarawak, 2006)
Doctoral degrees like the Doctor of Philosophy (PhD) have a longer history (in Britain, the first PhD at the University of London was awarded in 1857 and in the US, the PhD first appeared in Yale in 1861) but the Doctor of Business Administration (DBA) degree was introduced into American education around 20 years ago (Northeastern University Archives, 2003), and into the UK from the early 1990s (Boumer et ah, 2001; Bourner et. al., 2002). It has only recently appeared in the professional offerings in Australia (Maxwell and Shanahan, 1996, 1997: Perry and Cavaye 2002, Sarros et al., 2002). In Malaysia, PhDs have been offered mainly by public universities but DBAs are a recent trend, offered by some local public universities like UKM, USM, UUM, UiTM and private universities like MMU and OUM. In addition to that, DBAs are also offered by foreign Australian universities (like University of South Australia and University of Newcastle) through distance learning programmes with local colleges and Institute of Trainings & Development.